2015
DOI: 10.2139/ssrn.2568699
|View full text |Cite
|
Sign up to set email alerts
|

Investor Mood, Herding and the Ramadan Effect

Konstantinos Gavriilidis,
Vasileios Kallinterakis,
Ioannis Tsalavoutas

Abstract: In view of evidence linking herding and social mood, we examine whether the positive mood documented during Ramadan translates into higher herding compared to non-Ramadan days.Drawing on a sample of seven majority Muslim countries, we report significant herding during Ramadan in most of our sample markets. Additionally, we show that herding appears significantly stronger within rather than outside Ramadan for most tests whereby its significance is manifested on both Ramadan-and non-Ramadan-days. Overall, herdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…Interestingly, some findings support the claim that Islamic mutual funds perform better than socially responsible investments (Abdelsalam et al, 2014a(Abdelsalam et al, ,b, 2015. Overall results of these studies are in line with the theory of social norms which suggests that investors follow behavioural norms, belief/action of other communities, with special emphasis on religious beliefs (Akerlof, 1980;Gavriilidis et al, 2016). Overall results of these studies are in line with the theory of social norms which suggests that investors follow behavioural norms, belief/action of other communities, with special emphasis on religious beliefs (Akerlof, 1980;Gavriilidis et al, 2016).…”
Section: Performance Of Islamic Mutual Fundssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, some findings support the claim that Islamic mutual funds perform better than socially responsible investments (Abdelsalam et al, 2014a(Abdelsalam et al, ,b, 2015. Overall results of these studies are in line with the theory of social norms which suggests that investors follow behavioural norms, belief/action of other communities, with special emphasis on religious beliefs (Akerlof, 1980;Gavriilidis et al, 2016). Overall results of these studies are in line with the theory of social norms which suggests that investors follow behavioural norms, belief/action of other communities, with special emphasis on religious beliefs (Akerlof, 1980;Gavriilidis et al, 2016).…”
Section: Performance Of Islamic Mutual Fundssupporting
confidence: 71%
“…Nonetheless, it is not known with certainty whether the comparison between socially responsible investment and Islamic mutual funds will yield any differences in the findings. However, other literature attributes this result to the Ramadan effect, the consequence of which is abnormally high returns on Islamic mutual funds during Ramadan compared with the remaining periods of the year (Seyyed et al, 2005;Białkowski et al, 2012Białkowski et al, , 2013Al-Khazali, 2014;Mitchell et al, 2014;Gavriilidis et al, 2016). However, other literature attributes this result to the Ramadan effect, the consequence of which is abnormally high returns on Islamic mutual funds during Ramadan compared with the remaining periods of the year (Seyyed et al, 2005;Białkowski et al, 2012Białkowski et al, , 2013Al-Khazali, 2014;Mitchell et al, 2014;Gavriilidis et al, 2016).…”
Section: Performance Of Islamic Mutual Fundsmentioning
confidence: 99%
“…Gleason et al (2004) explored herding in the US market by employing data on nine sector S&P 500 Exchange Traded Funds listed on the American Stock Exchange. Gębka and Wohar (2013) in an international level revealed scarce evidence of irrational behavior for specific sectors, whereas Gavriilidis et al (2016) found significant herding behavior that is stronger during Ramadan in most of the seven Muslim countries of their sample. More recently, Balcilar et al (2014) for a sample of Gulf Arab stock markets documented significant evidence of herding.…”
Section: Brief Literature Reviewmentioning
confidence: 89%
“…It can lead to maximization of sentiment for the decisions of investment. Gavriilidis et al (2016) examined US investors' sentiment. The herding is significant and higher during Ramadan in most markets.…”
Section: Literature Reviewmentioning
confidence: 99%